Alveolar rhabdomyosarcoma of epididymis: A case report - Liang, Xiangyi; Wang, Shun; Li, Tao; Liu, Longlong; Duan, Yu; Luo, Yuting; Wang, Qing; Hu, Jianxin; Jiang, Kehua (Frontiers in Oncology, 2022)
Rhabdomyosarcoma (RMS) is a soft tissue tumor, which is the most common in the head, neck, limbs, and trunk. RMS originating from the epididymis is extremely rare. Herein, we reported a 34-year-old patient with RMS on the right epididymis. For this case, right epididymal mass resection was performed and intraoperative freezing suggested a malignant tumor. Right testicular radical resection was subsequently adopted, with right epididymal alveolar RMS being pathologically diagnosed. Alternating VAC/VI chemotherapy was given after surgery, and tumor recurrence has not been found so far.